Figurative Means in Forming the Publicity Discourse of Ibn Hazm Al-Andalusi (456 AH) - Jaafar , Mohsen Neama; Hussein, Sadiq Jaafar Abdul (Journal of Ecohumanism, 2024)
Rhetoric mainly aims to affect the recipients and bring ideas into their minds, employing figures of speech and other rhetorical means. It is one of the significant argumentative mechanics employed by a writer in delivering a speech. Therefore, the present study tracks figures of speech (simile, metaphor, and metonymy) and other persuasive means in the publicity discourse in the tradition of Ibn Hazm Al-Andalusi. It highlights their persuasive, argumentative impact in winning over the recipient and the attempt to build a publicity discourse based on stimulating the recipient to achieve persuasion towards the proposed idea and the desired purpose.